Security-Enhanced Electro-Optic Feedback Phase Chaotic System Based on Nonlinear Coupling of Two Delayed Interfering Branches - Cheng Wang; Yuefeng Ji; Hongxiang Wang; Lin Bai (IEEE Photonics Journal, 2018)
In this paper, a novel electro-optic feedback phase chaotic system based on nonlinear coupling of two delayed interfering branches is proposed and analyzed by numerical simulation. The feedback loop of the proposed system contains two delay branches and a Mach-Zehnder modulator. The chaotic voltages generated from two branches are nonlinearly converted in order to reduce their temporal correlations. The dynamic characteristics and the complexity of the generated chaotic signal are evaluated by the bifurcation diagram and permutation entropy, respectively. Besides, the simulated results show that the time-delay signature can be concealed effectively with a lower feedback gain, meanwhile the key space is extended considerably since more tunable parameters are nonlinearly coupled, thus the security can be improved greatly. Furthermore, the communication system based on the proposed scheme is discussed, and the results demonstrate that this system can be applied in secure communication.